Managing Online Classes in The Covid-19: Pre-Service Language Teachers’ Perceptions - Asep Nurjamin; Yustika Nur Fajriah; Lucky Rahayu Nurjamin (Jurnal Pendidikan Bahasa dan Sastra, 2022)
The shifting of offline to online classroom during Covid-19 Outbreak arose classroom management issues, especially in rural areas. From that point, this study aims to investigate pre-service language teachers’ perceptions on managing online classrooms.  Those respondents were five third graders in a university in Garut, West Java who were conducting pre-service teaching programs.  To achieve the goal of this study, qualitative research in the form of a case study design was employed. The data were collected using semi-structured interview.  The data were then analyzed using Creswell ‘s inductive analysis framework (2012) framed by the theory of classroom management from (Simonsen at al, 2014). As the result, teachers viewed that having a good classroom management is a must. Yet, they still needed to upgrade their self-concept as the teachers, as well as knowledge and skills in managing online classes; paying attention on the classroom conduciveness, translating the lesson plan into online teaching practice, as well as considering the quantity and quality of the task. The practical implication of this study is that relevant trainings may be addressed to pre-service teachers before they came to schools. Specifically, those trainings should cover the self-concept of pre-service teachers regarding their pedagogical competences, technological literacy, as well as the belief as the prospective teachers at the very first place.